93.4k views
2 votes
HELLP MEEEEEE

PLEASE

HELLP MEEEEEE PLEASE-example-1

1 Answer

3 votes

Answer:

x =
(5)/(4) + ( √(5) )/(4)

x =
(5)/(4) - ( √(5) )/(4)

Explanation:

Quadratic equation:


x = (-b +- √(b^2 - 4ac) )/(2a)

The equation is:


4x^2 - 10x + 5 = 0\\

So:

a = 4

b = -10

c = 5

Plug the variables into the quadratic equation:


x = (-(-10) +- √((-10)^2 - (4 * 4 * 5)) )/((2 * 4))


x = \frac{\sqrt{10 +- √(100 - 80) } }{8}


x = (10 + √(20) )/(8)

Divide both sides by 8:

10 ÷ 8 =
(5)/(4)


√(20) ÷ 8 =
(√(5))/(4)


(5)/(4) +-
(√(5))/(4)

This means that the solutions that satisfy the equation is:

x =
(5)/(4) + ( √(5) )/(4)

x =
(5)/(4) - ( √(5) )/(4)

Hope this helps!

User Taarraas
by
5.3k points